PEMULIHAN HAK KONSUMEN DI SEKTOR JASA PENDIDIKAN (STUDI KASUS YAYASAN PENDIDIKAN X MELAWAN DJONI SUKOHARDJO): Restore Consumer Rights in the Education Services Sector Case Study of X Education Foundation Against Djoni Sukohardjo - Magfirah, Wanda Pasya; Anggraini, Anna Maria Tri (AMICUS CURIAE, 2024)
Education is an important aspect of life that everyone need. To protect students in order to ensure the comfort of learning, so the students can be said to be consumers. The problem raised is how legal remedies can be restored consumer rights in education services sector and how the application of legal remedies restored consumer rights in the case of the X Education Foundation against Djoni Sukohardjo. Legal remedies that can be taken if consumers are not fulfilled by business actors can be resolved through the court or out of court based on Article 45 paragraph (1)(2) of CPL. If the business actor ignores the request for compensation, the consumer can file a lawsuit through BPSK or to the general court according to Article 23 of the CPL. Legal remedies to restore the rights of consumer Djoni Sukohardjo from the business actor X Education Foundation in Decision Number 005/A/BPSK-DKI/II/BPSK does not consider the contract between business actors and consumers. BPSK's decision was wrong in determining relationship between consumers and business actor. In this case, BPSK Decision does not consider the agreement between the two parties, considering the theory of the Privity of Contract and the principle of freedom of contract.